Monitoring cognitive change in multiple sclerosis using a computerized cognitive battery. Issue 4 (December 2018) - De Meijer, L; Merlo, D; Skibina, O; Grobbee, EJ; Gale, J; Haartsen, J; Maruff, P; Darby, D; Butzkueven*, H; Van der Walt, A
Background: Cognitive monitoring that can detect short-term change in multiple sclerosis is challenging. Computerized cognitive batteries such as the CogState Brief Battery can rapidly assess commonly affected cognitive domains. Objectives: The purpose of this study was to establish the acceptability and sensitivity of the CogState Brief Battery in multiple sclerosis patients compared to controls. We compared the sensitivity of the CogState Brief Battery to that of the Paced Auditory Serial Addition Test over 12 months. Methods: Demographics, Expanded Disability Status Scale scores, depression and anxiety scores were compared with CogState Brief Battery and Paced Auditory Serial Addition Test performances of 51 patients with relapsing–remitting multiple sclerosis, 19 with secondary progressive multiple sclerosis and 40 healthy controls. Longitudinal data in 37 relapsing–remitting multiple sclerosis patients were evaluated using linear mixed models. Results: Both the CogState Brief Battery and the Paced Auditory Serial Addition Test discriminated between multiple sclerosis and healthy controls at baseline ( p <0.001). CogState Brief Battery tasks were more acceptable and caused less anxiety than the Paced Auditory Serial Addition Test ( p <0.001). In relapsing–remitting multiple sclerosis patients, reaction time slowed over 12 months ( p <0.001) for the CogState Brief Battery Detection (mean change –34.23 ms) and Identification (–25.31 ms) tasks. Paced Auditory Serial Addition Test scores did not change over this time. Conclusions: The CogState Brief Battery is highly acceptable and better able to detect cognitive change than the Paced Auditory Serial Addition Test. The CogState Brief Battery could potentially be used as a practical cognitive monitoring tool in the multiple sclerosis clinic setting.